Erratum: Kemampuan Motorik Kasar: Aktivitas Outbound Pada Siswa Sekolah Dasar - Lutfi Nur; Rosarina Giyartini; Sumardi Sumardi (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.781 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.